(untitled) (PJDOL, 2023)
This cross-sectional study investigated the relationship among online-learning, time management and self-anxiety of university students for the duration of COVID-19 pandemic. A sample of 250 university students was selected from Lahore College for Women University, University of Punjab, Government College University, University of Central Punjab and University of Management and Technology by using stratified random sampling strategy. Online data were collected through Google Forms by using test eLearning related attitude scale (developed by Zabadi & Alawi, 2016), self-rating anxiety scale (developed by Zung, 1965), and time management behavior scale (developed by Macan & colleges, 1990). Data were analyzed through SPSS version 21. Reliability tests and inferential statistics were applied to find out the results. In inferential statistics, correlation and regression were used.